I, Alex Cross : a novel - Patterson, James, 1947- (New York : Little, Brown and Co., 2009)
Alex Cross is pulled out of a family celebration and given the awful news that a beloved relative has been found brutally murdered. Soon Alex and his girlfriend, Briana Stone, are facing down some very important, very protected, very dangerous people.
Includes an excerpt from Witch & wizard (11 p.).
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American detectives -- Fiction; Murder -- Investigation -- Fiction; Washington (D.C.) -- Fiction; Mystery fiction